Effectiveness of MRNA booster vaccine among healthcare workers in New York City during the Omicron surge, December 2021 to January 2022. (December 2022) - Robilotti, Elizabeth V.; Whiting, Karissa; Lucca, Anabella; Poon, Chester; Jani, Krupa; McMillen, Tracy; Freeswick, Scott; Korenstein, Deborah; Babady, N. Esther; Seshan, Venkatraman E.; Kamboj, Mini
Abstract: Objective: To describe effectiveness of mRNA vaccines by comparing 2-dose (2D) and 3-dose (3D) healthcare worker (HCW) recipients in the setting of Omicron variant dominance. Performance of 2D and 3D vaccine series against SARS-CoV-2 variants and the clinical outcomes of HCWs may inform return-to-work guidance. Methods: In a retrospective study from December 15, 2020 to January 15, 2022, SARS-CoV-2 infections among HCWs at a large tertiary cancer centre in New York City were examined to estimate infection rates (aggregated positive tests / person-days) and 95% CIs over the Omicron period in 3D and 2D mRNA vaccinated HCWs and were compared using rate ratios. We described the clinical features of post-vaccine infections and impact of prior (pre-Omicron) COVID infection on vaccine effectiveness. Results: Among the 20857 HCWs in our cohort, 20, 660 completed the 2D series with an mRNA vaccine during our study period and 12461 had received a third dose by January 15, 2022. The infection rate ratio for 3D versus 2D vaccinated HCWs was 0.667 (95% CI 0.623, 0.713) for an estimated 3D vaccine effectiveness of 33.3% compared to two doses only during the Omicron dominant period from December 15, 2021 to January 15, 2022. Breakthrough Omicron infections after 3D + 14 days occurred in 1, 315 HCWs. Omicron infections were mild, with 16% of 3D and 11% 2D HCWs being asymptomatic. Discussion: Study demonstrates improved vaccine-derived protection against COVID-19 infection in 3D versus 2D mRNA vaccinees during the Omicron surge. The advantage of 3D vaccination was maintained irrespective of prior COVID-19 infection status.